Desain Media Pembelajaran Interaktif berbasis Aplikasi dan Video Animasi (Smart App Creator 3) - Maftuh Ikhsan Nanda K; , Dina Mardiana; M. Kamaludin (Gunung Djati Conference Series, 2022)
The development of interactive learning media is a solutive effort in the midst of the progressivity of online learning during the COVID-19 endemic. Smart App Creator 3 is one of the applications that can be used in education to help students understand learning materials. This research aims to produce animation-based PAI learning media combined with application development without coding. This research uses the Research and Development ADDIE (Analysis, Design, Development, Implementation, and Evaluation). The results of this development research are in the form of interactive learning media products that have passed the validation test stage by material experts and media experts so that the media developed is suitable for use. The overall results of the validation test, the response of teachers and students obtained excellent results with details: (1) the material expert test got 92% very feasible results (2) the media expert test got 68% quite feasible results (3) the teacher's response got 92% and students got 86% of the total 28 students. This research concludes that PAI learning media based on the Smart App Creator 3 application is practicable to be used as a learning media and becomes a new innovation solution in education.